Drone technology as a tool for improving agricultural productivity - BHARTI, MEETALI; ., DEEPSHIKHA; BHARTI, SANDEEP (Journal of Soil and Water Conservation, 2021)
Drone is proving boon for managing agricultural production as it can focus on small crop fields at lower flight altitudes than other regular aerial vehicle to perform site-specific farm management operation with higher precision. The use of drone for agricultural applications is providing knowledge about fertilizing, seeding, multi-spectral imaging capacity to farmers who want to maximize their crop yields and reduce the amount they pay for labor. Drones will enhance farmer’s ability to obtain and utilize multi-spectral and hyper-spectral imagining to detect issues with crops before they harm crop yields. Drones also have the ability to autonomously lay seeds, fertilize soil, and spray pesticides. All farmers will have to do is program the drones to fly a certain pattern over their fields. This will effectively automate most of the farming process, including harvesting which will be done by autonomous tractors and other vehicles. Since drones will be able to fly at low altitudes too low for manned vehicles, the spraying of pesticides can be more exact, resulting in more precise spraying with less drift beyond the limits of the field sprayed. This paper presents an overview of research involving in the development of drone for agricultural management. Technologies, systems and methods are examined for in situ integration under Indian farming conditions.